2014
DOI: 10.1152/jn.00804.2013
|View full text |Cite
|
Sign up to set email alerts
|

Lag structure in resting-state fMRI

Abstract: Mitra A, Snyder AZ, Hacker CD, Raichle ME. Lag structure in resting-state fMRI. J Neurophysiol 111: 2374 -2391, 2014. First published March 5, 2014 doi:10.1152/jn.00804.2013.-The discovery that spontaneous fluctuations in blood oxygen level-dependent (BOLD) signals contain information about the functional organization of the brain has caused a paradigm shift in neuroimaging. It is now well established that intrinsic brain activity is organized into spatially segregated resting-state networks (RSNs). Less is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
367
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 168 publications
(400 citation statements)
references
References 96 publications
(109 reference statements)
32
367
1
Order By: Relevance
“…For instance, SPW-Rs, slow waves, and many other neural processes are enriched in (awake) post-task learning periods as well as sleep [68,73,74]. In fact, we have indeed found that propagation patterns in rs-fMRI are sensitive to physiological changes in state, including before versus after motor learning tasks [26], eyes open versus closed [26] and most dramatically, wake versus slow wave sleep [45]. These findings suggest that the propagation structure of rs-fMRI can be used to reveal fundamental neural 'events' or processes in spontaneous activity; however, future multi-modal studies are necessary to investigate whether events such as SPW-Rs underlie distinct BOLD signal propagation patterns.…”
Section: Biological Mechanismmentioning
confidence: 57%
See 4 more Smart Citations
“…For instance, SPW-Rs, slow waves, and many other neural processes are enriched in (awake) post-task learning periods as well as sleep [68,73,74]. In fact, we have indeed found that propagation patterns in rs-fMRI are sensitive to physiological changes in state, including before versus after motor learning tasks [26], eyes open versus closed [26] and most dramatically, wake versus slow wave sleep [45]. These findings suggest that the propagation structure of rs-fMRI can be used to reveal fundamental neural 'events' or processes in spontaneous activity; however, future multi-modal studies are necessary to investigate whether events such as SPW-Rs underlie distinct BOLD signal propagation patterns.…”
Section: Biological Mechanismmentioning
confidence: 57%
“…Critically, the mean value in each of the off-diagonal blocks in the TD matrix is very nearly zero [26,45]. If one RSN were systematically earlier than another RSN, the expected offdiagonal block mean would be non-zero.…”
Section: Temporal Lags Analysismentioning
confidence: 95%
See 3 more Smart Citations